Re-examining Indonesia’s Nickel Export Ban: Does it Violate the Prohibition to Quantitative Restriction? - Yetty Dewi; Mikaila Jessy Azzahra (Padjadjaran Journal of International Law, 2022)
The fundamental principles adopted by the WTO are free trade and trade liberalization, realized through the reduction of trade barriers like quantitative restrictions. This paper examines the parameters of a measure that can be construed as a quantitative restriction in violation of WTO law. It also examines whether Indonesia’s measures in prohibiting the export of nickel ores and imposing domestic processing requirements violate WTO law. The statutory and case study approaches were used to determine and analyze Indonesia’s measures. The parameter for quantitative restriction is imposed in Article XI: I of the GATT 1994. The parameter warrants that a measure shall be in the form of prohibitions or restrictions apart from duties, taxes, or charges. The measure must also be enacted through quotas, import or export licenses, or other measures such as import or export prohibitions. Finally, the nature of the measure must be limited in amounts. However, a measure that fulfills such parameters may not violate WTO law if it is justified under exclusionary articles under the GATT 1994. The paper concludes that Indonesia’s measures above constitute quantitative restrictions, as they fulfill the parameters above. However, there is a possibility that the measures may not violate WTO law. This is because the measures also fulfil the parameters of justifications under Article XX (g) of the GATT 1994 on general exceptions and to a lesser extent under Article XI: (2)(a) of the GATT 1994 on the exception to quantitative restrictions.